Acquired enamel pellicle and biofilm engineering with a combination of acid-resistant proteins (CaneCPI-5, StN15, and Hemoglobin) for enhanced protection against dental caries - in vivo and in vitro investigations - Araujo, Tamara Teodoro; Dionizio, Aline; Carvalho, Thamyris Souza; Boas Feitosa, Chelsea Maria Vilas; Vertuan, Mariele; Câmara, João Victor Frazão; Henrique-Silva, Flavio; Marchetto, Reinaldo [UNESP]; Chiaratti, Marcos Roberto; Santos, Angélica Camargo; Alves, Lindomar Oliveira; Ferro, Milene [UNESP]; et al. (Springer Nature, 2024)
Objective: This study was designed in two-legs. In the in vivo, we explored the potential of a rinse solution containing a combination (Comb) of 0.1 mg/mL CaneCPI-5 (sugarcane-derive cystatin), 1.88 × 10− 5M StN15 (statherin-derived peptide) and 1.0 mg/mL hemoglobin (Hb) to change the protein profile of the acquired enamel pellicle(AEP) and the microbiome of the enamel biofilm. The in vitro, was designed to reveal the effects of Comb on the viability and bacterial composition of the microcosm biofilm, as well as on enamel demineralization. Materials and methods: In vivo study, 10 participants rinsed (10mL,1 min) with either deionized water (H2O-control) or Comb. AEP and biofilm were collected after 2 and 3 h, respectively, after rinsing. AEP samples underwent proteomics analysis, while biofilm microbiome was assessed via 16 S-rRNA Next Generation Sequencing(NGS). In vitro study, a microcosm biofilm protocol was employed. Ninety-six enamel specimens were treated with: 1)Phosphate-Buffered Solution-PBS(negative-control), 2)0.12%Chlorhexidine, 3)500ppmNaF and 4)Comb. Resazurin, colony-forming-units(CFU) and Transversal Microradiography(TMR) were performed. Results: The proteomic results revealed higher quantity of proteins in the Comb compared to control associated with immune system response and oral microbial adhesion. Microbiome showed a significant increase in bacteria linked to a healthy microbiota, in the Comb group. In the in vitro study, Comb group was only efficient in reducing mineral-loss and lesion-depth compared to the PBS. Conclusions: The AEP modification altered the subsequent layers, affecting the initial process of bacterial adhesion of pathogenic and commensal bacteria, as well as enamel demineralization. Clinical relevance: Comb group shows promise in shaping oral health by potentially introducing innovative approaches to prevent enamel demineralization and deter tooth decay.
Keywords: Acquired enamel pellicle; Biofilm; CaneCPI-5; Dental caries; Hemoglobin; Statherin